Сравните значения выражений -0,8x - 1 и 0,8x - 1 при x = 6
-0,8x - 1 при x = 6 будет равен -0.8 * 6 - 1 = -5.8
0,8x - 1 при x = 6 будет равен 0.8 * 6 - 1 = 3.8
Получается -0,8x - 1 < 0,8x - 1
-0,8x-1=0,8x-1
-0,8x-1=-0,8*6-1=4,8-1=3,8
0,8x-1=0,8*6-1=4,8-1=3,8
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Сравните значения выражений -0,8x - 1 и 0,8x - 1 при x = 6
-0,8x - 1 при x = 6 будет равен -0.8 * 6 - 1 = -5.8
0,8x - 1 при x = 6 будет равен 0.8 * 6 - 1 = 3.8
Получается -0,8x - 1 < 0,8x - 1
-0,8x-1=0,8x-1
-0,8x-1=-0,8*6-1=4,8-1=3,8
0,8x-1=0,8*6-1=4,8-1=3,8